Conservation status assessment of the highest forests in the world: Polylepis flavipila forests as a case study - Ames-Martínez F.N. (2021)
This research was supported by Consejo Nacional de Ciencia, Tecnolog?a e Innovaci?n Tecnol?gica-CONCYTEC, under Grant 382-2019-FONDECYT-DE; Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica [382-2019-FONDECYT]; We thank the ?Servicio Nacional Forestal y de Fauna Silvestre? and the ?Servicio Nacional de ?reas Naturales Protegidas por el Estado? for providing authorizations for research under R.D.G. No. 037-2017-SERFOR/DGGSPFFS and R.D. 009-2018-SERNANP-DGANP, respectively. Likewise, we are grateful to Wendy Carolay Navarro Romo, Ciro Ricardo Paredes Huam?n (Negrito) and Jimy Ronie Llacuachaqui Rodr?guez (Timys) for contributing to field work and making it so much fun.